Evaluation of acrylic acid grafting on the loading and release of scopolamine butylbromide from polymeric matrices for future sialorrhea treatment - Morise, Beatriz Tiemi [UNESP]; Mutch, Alexandra Louise; Garms, Bruna Cambraia; Herculano, Rondinelli Donizetti [UNESP]; Grøndahl, Lisbeth (Wiley, 2021)
Sialorrhea is a disorder which causes an increase in salivation. Scopolamine butylbromide (SBB) can be administrated to treat sialorrhea and its transdermal application minimizes the occurrence of side effects. This work compared SBB adsorption and release from two polymer matrices, polycaprolactone and natural rubber latex, as well as the matrices modified by gamma irradiation-induced graft copolymerization of acrylic acid (AAc). Grafting with AAc-introduced carboxylate groups onto the surface of the matrices evident from chemical analysis and resulted in increased hydrophilicity evident from contact angle measurements. SBB adsorbed to the matrices without changing its structure and for the AAc-grafted matrices this was governed by electrostatic interactions. Higher SBB loading was observed for the AAc-grafted matrices while SBB release was slower for the non-grafted matrices than the grafted matrices. The four different matrices produced are candidates for the development of a transdermal drug delivery system.